ثقافة وقف المخطوطات الإباضية بخزانات وادي مزاب - حاج أمحمد، يحيى بن بهون (المجلس الأعلى للغة العربية, 2021)
يزخر وادي مزاب بالجنوب الجزائري بعديد المكتبات وخزانات المخطوط الخاصة والعامة، إذ في كل قرية من قرى وادي مزاب السبعة تقريبا توجد كنوز تراثية مخطوطة ووثائق ومطبوعات نادرة... ومع انطلاق حركة فهرسة الخزانات المحلية منذ تسعينيات القرن الماضي وازدهارها حاليا، اكتشفت العديد من النسخ المخطوطة النفيسة في شتى فنون العلم تقريبا، ومع ازدياد الاهتمام بهذا التراث الخالد وجب الاهتمام أيضا بثقافة المخطوط عموما من نسخ وتجليد وتملك وتحبيس... تتعرض هذه الورقة البحثية إلى التعريف بداية بأشهر خزانات المخطوط بوادي مزاب؛ مركزة على مقتنيات الخزانة العامة بغرداية، وتحاول تتبع حركة تملك (Ex-libris) المخطوطات بها وتحبيسها على العام والخاص (خزانات أو أشخاص) (mettre en biens de mainmorte, constituer habous) (ex_dono) وبهذا يتم التعرف على الأعلام المحليين الذين أسهموا في الحركة العلمية ماديا أو أدبيا، ممن امتلكوا المخطوطات وأوقفوها على ذرياتهم أو على طلبة العلم في المساجد والمحاضر ودور التعليم العامة والخاصة، وكذا تتبع اهتمام الملاك المحليين بالمخطوطات وحركة اقتناء وجلب المخطوطات من الأماكن البعيدة... آملا أن يكون هذا البحث إضافة نوعية لمجال بحث المهتمين بالتراث الإباضي المخطوط خصوصا وبثقافة المخطوطات عموما، وخدمة الباحثين وكل من يريد التعرف على الكنوز المعرفية المخطوطة بمزاب.
The south of Algeria, M’zab Valley is thriving of several local and private Manuscript libraries. In each town of the M’zab valley, merely all the seven towns, there is a treasure of manuscripts and rare documents. The initiative of indexing local libraries since the 1990s of the recent century has allowed me to discover precious and valuable manuscript copies in different field of research and science. starting from the importance of this valuable heritage, it is very important also to care more about it and treat the manuscripts through making copies, binding them as books, and so forth… The present research paper presents the main known libraries in M’zab Valley, more specifically the local library in Ghardaïa town. It investigates the process of ex-libris and ex-dono of these documents. As a result, we shall be conversant of the scholars and personalities that served the scientific movement literally and financially. Those people owned the manuscripts to let it as Waqf for their relatives and students in mosques and in local and private education schools. The study allows to know more about the process of owning such documents notably selling and transferring of the manuscripts from different countries. The researcher is willing to serve the researcher community in the field of manuscripts in general and especially the cultural Ibadit Heritage. It is a resource for every researcher who wants to discover the cognitive treasure of M’zab Valley.
Keywords: الوقف الإسلامي -- ثقافة الوقف -- وقف المخطوطات -- المخطوطات الإباضية -- التراث الإباضي المخطوط -- خزانات المخطوطات -- وادي مزاب -- الجزائر